PWE-014 Jesrey Flexible Sigmoidoscopy Bowel Cancer Programme: One Year's Experience. (9th June 2014) - Duku, M; Ng, D; De George, S; Hughes, T; Tierney, K; Turnbull, S; Diggle, L
Abstract : Introduction: Randomised control trials (RCTs) have demonstrated that once-only flexible sigmoidoscopy (FS) between ages of 55 to 64 reduces both incidence and mortality from colorectal cancer. A key marker of quality in FS screening is adenoma detection rate (ADR), which relies on effective bowel preparation and good technique. The States of Jersey introduced once-only FS at age 60 in February 2013. This study aims to evaluate the one-year outcomes of the programme. Methods: Jersey residents aged 60 were invited by post to participate in the programme. Responders were telephone pre-assessed for eligiblity and bowel habit and assigned one of two bowel cleansing regimes; two fleet enemas + senna/bisacodyl or moviprep. FS were performed, unsedated, by two experienced gastroenterologists using paediatric colonoscopes, with the aim of visualising at least 60cm (straightened endoscope) of the left colon. Clients with poor bowel preparation had additional fleet enema and re-scoped on the same day or returned on a later day following moviprep. All polyps =1 cm were removed during FS. Indication for colonoscopy was the presence of high-risk lesions (adenoma =1 cm, adenoma with high grade dysplasia or a villous component and = 3 adenomas). After FS, clients were given a questionnaire, which included a pain score. Results: 768 clients were invited. 60 were ineligible. 453 had the FS. The uptake was 69.2% and overall ADR was 15.7% (Table 1 ) which are higher than in the RCTs. FS was well tolarated. Only 36 (13.9%) required entonox. 79% reported no or mild discomfort and only 1% reported severe discomfort. 1 client had an incomplete examination due to pain. 435 (96.03%) had 2 fleet enemas plus senna or bisacodyl and 18 (3.97%) had moviprep as the first bowel prep. The quality was excellent or good in 83%. Only 32 (7%) had poor prep and needed repeat bowel preperation. There were no major complications during bowel preperation or the FS. 1 patient reported abdominal cramps during bowel preparation and 2 and vasovagal episodes immediately after the FS. None required hospital admission. Conclusion: FS screening using two enemas is acceptable and safe. Better bowel preparation and complete examination of the left colon contributed to the high ADR. The impact of the uptake and high ADR on the incidence and mortality of CRC in Jersey will likley be greater than that seen in the RCTs. Disclosure of Interest: None Declared.